Feasibility Analysis of Koi Fish (Cyprinus carpio) Hatchery Business at Batu Kumbung Fish Seed Center (BBI), Lingsar Subdistrict - Alim, Sahrul; Muahiddah, Nuri (Program Studi Budidaya Perairan Universitas Mataram, 2023)
Koi fish (Cyprinus carpio) is one of the potential freshwater ornamental fish commodities that can be cultivated. This freshwater ornamental fish has several advantages, including easy maintenance, ability to survive in low oxygen water, and ability to produce high-quality eggs. The purpose of this research is to assess the feasibility of the breeding activities conducted at BBI Batu Kumbung through economic analysis. The research method used in this study is